SYNTHESIS AND CHARACTERIZATION OF SOME COMPLEXES WITH IBUPROFENYL HYDRAZONE - Amira J. Al_Shaheen; Miaad A. Al Mula (Journals Park Publishing, 2022)
Fourteen new metal complexes have been synthesized from ibuprofenyl hydrazide and vanillin or acetophenone ligands (L1 and L2) and used in preparing the corresponding Cobalt(II) , Nickel(II) , Copper(II) , Zinc(II) , Cadmium(II) complexes. The resulted complexes have been characterized by different physiochemical methods including elemental analyses, IR  electronic spectra , magnetic moment measurements , molar conductance, and X-ray powder diffraction measurements, the ligands have been investigated by NMR spectra . Furthermore, the complexes have been found to have the formulas  [M(L)2Cl2]  where, M= Co(II) , Ni(II) , Cu(II) and Zn(II). whereas, the formula  [M(L)2(H2O)2](NO3)2 , M= Co(II) , Ni(II) , [Cd(L)2]Cl2 ; L = L1 or L2 . Infrared spectral data suggest that the two ligands behave as a bidentate ligand with O,N, donor atoms towards the metal ions  . Based on the above physicochemical measurements, the complexes have octahedral and tetrahedral geometries.